Epidemiology of respiratory viruses among children during the SARS-CoV-2 pandemic: A systematic review and meta-analysis - Dallmeyer, Leonie K.; Schüz, Marit L.; Fragkou, Paraskevi C.; Omony, Jimmy; Krumbein, Hanna; Dimopoulou, Dimitra; Dimopoulou, Konstantina; Skevaki, Chrysanthi (International journal of infectious diseases, 2024)
•Enterovirus/rhinovirus and human respiratory syncytial virus (HRSV) were the most prevalent respiratory viruses among children.•Subanalysis revealed differences in regional, seasonal, and age group distribution.•Highest prevalence was found in children up to 1 year old.•The prevalence of HRSV increased in the second half of the pandemic. This meta-analysis aimed to assess the prevalence of respiratory viruses among children under the special conditions of the COVID-19 pandemic. Five databases were systematically searched to assess the pooled prevalence of various respiratory viruses in different age groups, regions, seasons, and in patients with and without confirmed SARS-CoV-2 coinfection. Moreover, we looked at the virus distribution in the first and second half of the pandemic and countries with distinct economic status. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were followed, and the systematic review was registered on PROSPERO (CRD42022379297). Enterovirus/rhinovirus and human respiratory syncytial virus (HRSV) were the most prevalent pathogens among children. The prevalence of HRSV increased in the second half of the pandemic. The prevailing viruses vary according to the SARS-CoV-2-coinfection status, season, region, and country´s economic status. This meta-analysis shows the epidemiology of respiratory viruses other than SARS-CoV-2 in children aged 0 to 12 years during the COVID-19 pandemic. Because major events, such as a pandemic, can alter epidemiology patterns, it is important to know them to improve health education measures, develop vaccines and medicines for vulnerable groups, as a guide for prevention strategies, and help with clinical decisions.